Integrated neural technologies: solutions beyond tomorrow - Mohamed, Wael Mohamed Yousef; Chatterjee, Indranath; A Kamal, Mohammad (Neurotak Publishing, 2020)
Neuroscience is an exciting area in which, at a fast rate, revolutionary advances materialise. Neurotechnology is interesting and contentious at the same time, as one of its aims is to "wire" human brains directly into computers. Neurotechnology is defined as the assembly of methods and instruments which allow a direct connection to the nervous system of technical components. These instruments are electrodes, machines or smart prostheses. They are designed to record and/or "translate" impulses from the brain into control instructions, or to modify brain function through the application of electrical or optical stimulation. The emergence of neuro-technologies is interdisciplinary. It supports the amalgamation of neurobiology with atomic, nano- and micro-sciences, as a fascinating path for significant development in the neuroscience domain. It poses a scientific foundation for potential therapeutic strategies